Pengaruh Big Data dan Cyber Security Disclosure terhadap Shari’ate Value Added (Studi Empiris pada Bank Umum Syariah di Indonesia Periode 2019-2023) - Sherlin Kamilia; Supriyono (Institut Ilmu Sosial dan Manajemen Stiami, 2026)
This research aims to determine the influence of big data and cyber security disclosure on shari’ate value added on Islamic commercial banks in Indonesia for the 2019-2023 period. This research is quantitative research which was measured using multiple linear regression analysis methods via Eviews 10. The data used in this research was secondary data. The data collection technique used was documentation techniques through financial reports and annual reports published by Islamic commercial banks for the 2019-2023 period. Hypothesis testing was done by using the t test, F test, and coefficient of determination test (R2). The results of the study proved that big data partially has no effect on shari’ate value added, cyber security disclosure partially has an effect on shari’ate value added, big data and cyber security disclosure simultaneously have an effect on shari’ate value added. Keywords: Big Data; Cyber Security Disclosure; Shari'ate Value Added; Islamic Commercial Banks